How Balanced Discussion Shapes Knowledge, Public Perceptions, and Attitudes: A Case Study of Deliberation on the Los Alamos National Laboratory - Gastil, John W. (My University, 2006)
Prior research has demonstrated the potential impact of carefully orchestrated public forums, such as National Issues Forums and deliberative polls. Many public discussions, however, lack the careful design and focused purposes of such events, and it remains unclear to what extent informal conversations and public meetings can produce the same knowledge gains and attitude changes. If public meetings and conversations are to have similar impacts, they may require important features of deliberation, such as the balanced presentation of alternative viewpoints. To explore the associations of perceived discussion balance with issue knowledge, attitude integration, and the misperception of public attitudes, this study used cross-sectional survey data regarding how New Mexicans view Los Alamos National Laboratory (LANL). The findings confirm the significance of perceived discussion balance for many—but not all—of the positive cognitive impacts of public discussions and conversations. Moreover, these findings show that deliberation is more scarce for some sub-publics than others, and the deliberative experience may be least common for those who need it most.